Individualism-collectivism as predictors of prejudice toward Gypsies in Spain - Gouveia, Valdiney V. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2012)
The associations between individualism-collectivism and prejudice have yielded mixed findings. Triandis (1995) argues that prejudice and discrimination are more likely among collectivists than individualists, and that the vertical attribute (emphasizing hierarchy) of both individualism and collectivism is more related to negative attitudes toward out-groups. The present study examines the predictive power of individualism and collectivism to explain measures of prejudice toward a minority out-group (gypsies) among the general population of a collectivist culture (Spain). Results indicate that individualists are more likely to express prejudice toward gypsies, whereas collectivists favor more positive thoughts, feelings, and behaviors toward this out-group. The findings also indicate that the horizontal attribute (emphasizing equality) was more important when assessing individualism-collectivism relations with prejudice in Spain. In such collectivistic culture, individualism is more likely to instigate prejudice, while collectivism more likely to inhibit it. These findings support other research showing that individualists are more likely to prejudice and discriminate, but contradict Triandis’ expectation that vertical collectivists are more likely to express negative attitudes toward out-groups (followed by vertical individualists, horizontal collectivists and horizontal individualists). Theoretical explanations for the findings are discussed.